Revised definitions of the anthiadine fish genera Mirolabrichthys Herre and Nemanthias Smith, with description of a new genus (Teleostei: Serranidae) - Gill, Anthony C. (Zootaxa, 2022)
Previously regarded as a subgenus of Pseudanthias Bleeker, Mirolabrichthys is rediagnosed and restricted to three species, the type species, M. tuka Herre & Montalban, along with M. pascalus (Jordan & Tanaka) and M. evansi (Smith). Five other species previously classified in Mirolabrichthys are reallocated to Nemanthias Smith, which beforehand had included only the type species, N. carberryi Smith: N. bartlettorum (Randall & Lubbock), N. bicolor (Randall), N. dispar (Herre), N. ignitus (Randall & Lubbock), and N. regalis (Randall & Lubbock). The remaining nine species previously placed in Mirolabrichthys are classified in a new genus, Pyronotanthias: P. lori (Lubbock & Randall), P. aurulentus (Randall & McCosker), P. bimarginatus (Randall), P. flavoguttatus (Katayama & Masuda), P. parvirostris (Randall & Lubbock), P. privitera (Randall & Pyle), P. smithvanizi (Randall & Lubbock), P. timanoa (Victor, Teitelbaum & Randall) and P. unimarginatus (Randall). Synapomorphies supporting monophyly of each genus are provided, along with generic descriptions and character summaries for included species. Characters supporting relationships of the three genera to each other and to other anthiadines are discussed.